THE EFFECT OF TAX SUPERVISION AND TAX COLLECTION ON OBEDIENCE TO PAY TAXES AND TAX REVENUE - Basrowi Basrowi (INDONESIAN JOURNAL OF ACCOUNTING AND GOVERNANCE, 2019)
The purpose of this study was to determine the effect of tax supervision and tax collection bothpartially and simultaneously on the compliance of taxpayers and their implications for tax revenue.The type of research used in this study is a type of causality research, namely research that aims todetermine the effect of independent variables on the dependent variable. However, the method used inthis research is a quantitative approach. The data collection technique used in this study is by usingsecondary data from the Pratama Tax Office of Lampung Province, specifically from the InspectionSection and the 2017 and 2018 Billing Section. Data were analyzed using the SPSS version 18 andLisrel programs. Based on the results of data analysis it was concluded that there were significanteffects both partially and simultaneously between tax supervision, tax collection, taxpayer compliancewith tax revenue.